KEADAAN RUMAH, KEBIASAAN MAKAN, STATUS GIZI, DAN STATUS KESEHATAN BALITA DI KECAMATAN TAMANSARI, KABUPATEN BOGOR - Desti Sagita Putri; Dadang Sukandar (Jurnal Gizi dan Pangan, 2012)
The general objective of this study was to analyze house condition, eating habits, nutrition nutritional status and health status of underfive children in Tamansari, Bogor. This research is part of the research entitlet “A Multi-Approach Intervention to Empower and Posyandu Nutritional Program to Combat Malnutrition Problem in Rural Areas” was conducted on February 2012 by a cross sectional study design. Subject of this study were 120 mothers and underfive children selected by purposive sampling with criterias (1) family who have underfive children, (2) registered as posyandu participant, (3) willing for interviewed. The primary data was number of family member, income, age, education, occupation, underfive children gender and age, housing conditions, eating habits, nutritional and health status. The analysis was carried out by Structural Equation Modeling (SEM). The house condition had significant effect on nutritional status (p<0.05). Eating habits had significant effect on nutritional status (p<0.05). Nutritional status had significant influence to health status (p<0.05).